Temporal Progression of Excitotoxic Calcium Following Distal Middle Cerebral Artery Occlusion in Freely Moving Mice - Nelson, Ashley N.; Calhoun, Michael S.; Thomas, Ankur M.; Tavares, Jennifer L.; Ferretti, Daniel M.; Dillon, Gregory M.; Mandelblat-Cerf, Yael (Frontiers in Cellular Neuroscience, 2020)
Ischemic stroke is recognized as one of the leading causes of adult disability, morbidity, and death worldwide. Following stroke, acute neuronal excitotoxicity can lead to many deleterious consequences, one of which is the dysregulation of intracellular calcium ultimately culminating in cell death. However, to develop neuroprotective treatments that target neuronal excitotoxicity, it is essential to know the therapeutic time window for intervention following an ischemic event. To address this question, the current study aimed to characterize the magnitude and temporal progression of neuronal intracellular calcium observed following distal middle cerebral artery occlusion (dMCAO) in mice. Using the calcium fluorescence indicator, GCaMP, we tracked neuronal population response in freely moving animals immediately following dMCAO in both the core infarct and peri-infarct regions. Our results demonstrate that calcium excitotoxicity following artery occlusion can be generally characterized by two phases: a transient increase in activity that lasts tens of minutes, followed by a long, slow sustained increase in fluorescence signal. The first phase is primarily thought to represent neuronal hyperexcitability, defining our therapeutic window, while the second may represent gradual cell death. Importantly, we show that the level of intracellular calcium following artery occlusion correlated with the infarct size at 24 hours demonstrating a direct connection between excitotoxicity and cell death in our stroke model. In addition, we show that administration of the NMDA antagonist MK-801 resulted in both a decrease in calcium signal and a subsequent reduction in the infarct size. Altogether, this study represents the first demonstration in freely moving animals characterizing the temporal progression of toxic calcium signaling following artery occlusion. In addition, these results define a critical time window for neuroprotective therapeutic intervention in mice.